Hermite-Hadamard Type Inequalities Associated with Coordinated ((s,m),QC)-Convex Functions - Yu-Mei Bai; Shan-He Wu; Ying Wu (Journal of Function Spaces)
In this paper, we introduce the definition of coordinated ((s,m),QC)-convex function and establish some Hermite-Hadamard type integral inequalities for coordinated ((s,m),QC)-convex functions.